(3EOGQI GdJShjb GdMOjKs (3eONd eYGUQs - (3GdRYHj(B, (3Ydj adGM s ((3YeGfs (3OGQ GdeSjQI ddfTQ hGdJhRjY hGdWHGYIs, 2022)
(3dbO LGA gPG GdcJGH GdefgLj HaUhdg cNGQWI WQjb ddEOGQI GdMOjKI ddJShjb, gGOakG Edi JhVjM GdOhQ GdgGe hGdMjhj hJSdjW GdVhA Ydi GdeaGgje GdCSGSjI hGdCWQ GdacQjI hGdhXGFa GdQFjSjI dgG aj eMGhdI LGOI dHfGA gjcd eJfGSb eJcGed jeqcf GdHGMKjf hCUMGH GdGNJUGU ef GdEdeGe HeMJhi gPG GdehVhY GdYdej hGdacQj GdeYGUQ dchfg GdeQJcR GdCSGSj dcaGAI haYGdjI GdCOGA aj efXeGJ GdCYeGd cGaI UZjQI Ch cHjQI, hWfjI Ch YGdejI, gGOaI ddQHM Ch ZjQ gGOaI dg, hPdc JMbjbkG ddfLGM hGdGROgGQ hVeGfkG ddHbGA hGdGSJeQGQ hHfGkA ddejRI GdJfGaSjI hGdSeYI hGdTgQI hhUhdkG ddbjGOI hGdQjGOI aj GdShb(B. (3hJLSjOkG dgPg GdCgOGa hdCf gPG GdcJGH dG jTcd hSjdI aMSH Hd GHYO ef Pdc HcKjQ LOkG agh efgL JWHjbj eJcGed eYGUQ dEOGQI GdJShjb abO LGAJ gjcdjJg echfI ef GKfj YTQ aUdkG(B. s
Keywords: (3GdJShjb (B- (3EOGQIs; (3GdJShjb GdGdcJQhfjs